THE DEVELOPMENT OF EXERCISES TO IMPROVE TEACHER TRAINEES’ INTERACTIVE SKILLS - Pelletier, Jean-Pierre (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2021)
This paper outlines the results of the operational phase of a research and development project (Harvey and Loiselle, 2009). It explains how practical exercises supporting the development of teacher trainees’ interactive classroom management skills were tested through a collaborative process and underscores the exercises’ potential to develop participants’ reflective skills. This research follows the work of authors who established close links between improvisation and teaching and of those who highlighted the benefits of an improv training program on the development of classroom management skills.